Design and Field Application of a Lifetime Metering Device for Distribution Transformers Based on Hotspot Temperature - Dirik, Hasan; Gezegin, Cenk; Ozgoenel, Okan; Geyikoglu, Ali; Sancaktar, Idris (Gazi Univ, 2024)
Solar air collectors The most important parameter determining real lifetime of transformers, which are generally designed to have a lifespan of around 30 years, is excessive temperatures exposed to winding insulations. If the temperature of winding insulation exceeds the critical temperature, aging rate decreases below the expected value, while it is under the critical temperature the aging becomes much slower. Therefore, by accurately monitoring winding temperature of a transformer, it is possible to accurately determine the aging rate and remaining life. In this study, design and field application of a lifetime metering device that developed based on this information is explained. The calculation method first calculates average winding temperature using winding resistance that is obtained by the real -time currents and voltages. Next, the winding hot-spot temperature is calculated using top oil, ambient and average winding temperature. Last, the aging rate and used/remaining life values of transformer are obtained by winding hot-spot temperature. The device can also generate warning and alarm signals for user depending on excessive temperature, and perform energy efficient cooling control. The developed device can not only present the data to user with a touch screen on it, but also transfer it to a server via wireless internet connection.
Dirik, Hasan/0000-0003-0625-7213; Gezegin, Cenk/0000-0002-4442-904X; Sancaktar, Iis/0000-0002-4790-0124;
Keywords: Transformer; Lifetime Meter; Hot-Spot Temperature; Insulation Aging